Percutaneous vesiculodeferentography in the diagnosis of male infertility: A review of our results and the data reported in the literature - Solivetti, F.M. (Elsevier, 2008)
Vesiculodeferentography was used in the past to evaluate suspected cases of obstruction of the seminal ducts. Over the years, numerous attempts have been made to improve the technique used to perform this examination and to render it less invasive. Its use is currently indicated in selected cases, where it is combined with functional studies like seminal tract washout and followed by immediate interventions to correct the alterations revealed. Vesiculodeferentography includes collection of the contents of the seminal vesicles, which can later be used in vitro assisted fertilization procedures.